Analysis of landing error scoring system during drop vertical jump on anterior cruciate ligament injury risk factors in elite fencers - Cho. J. H.; Chung, J.; Lee, K. H.; Lim, B.-O. (The Korean Journal of Sports Medicine, 2018)
Purpose: The aim of this study was to identify the differences of gender and detail items by using landing error scores during drop vertical jumping that can be used in the field for elite fencers and to use them as basic data for prevention of injury. Methods: The subjects were 42 elite fencers. Independent sample t-test was used to compare the landing error scoring system (LESS) score between the groups. In order to compensate for errors that may occur in multiple comparisons, they are corrected through the Bonferroni collection. The significant differences between the groups were evaluated using Cohen effect difference, and one-way analysis of variance was performed for differences in epee, fleuret, and sabre. Results: The comparison of landing error scores between male and female fencer groups showed that the knee valgus angle at initial contact, lateral trunk flexion angle at initial contact, stance width-narrow, foot position-toe out, symmetric initial foot contact, in the total score of LESS items, female fencer group was higher and statistically significant difference was found. Conclusion: In the case of fencing players, there is no significant difference in the LESS scores according to the items. However, when comparing gender, female fencers have higher LESS scores than male fencers; female fencers should be more careful in preventing injuries.